Optimal Unemployment Policy - Nicholas Lawson (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
A vast literature studies the optimal design and generosity of unemployment insurance (UI). However, UI is just one of the variety of programs used in developed countries around the world to deal with unemployment, though unemployment programs other than UI have been subjected to much less welfare analysis. My paper adds to a small but growing literature that evaluates the welfare implications of a wider range of unemployment programs, while incorporating two empirically relevant phenomena that have generally been ignored in this literature: private consumption smoothing and fiscal externalities from income taxes. I estimate a job search model using indirect inference with data from the March CPS, and simulate the model to evaluate a wide variety of policy reforms. I show that monitoring and job search assistance (JSA) play important roles, with welfare impacts at least as large as that of the UI replacement rate. The optimal combined policy incorporates more short-term insurance as well as increased monitoring of search and expanded provision of JSA. I also find that general and partial equilibrium results are generally similar, as programs that raise bargained wages also reduce job-creation, with impacts on welfare that nearly offset.
Keywords: 330